Analysıs Of Internatıonal Poultry Trade Dıspute Between Indonesıa And Brazıl Under Gatt - Irvanaries Irvanaries; Rahmi Ayunda (Universitas Internasional Batam, 2021)
GATT As the treaty is a soft law, there were many case of where states did not fully ratify the treaty which then leads to dispute. One of the most iconic cases is the poultry dispute between Indonesia and Brazil in regards of Poultry trade. The policy that is being disputed is known as the quantitative restrictions. The purpose of the paper is to analyze how is the dispute resolved, and what is the consequences of the dispute Both ideas will be explained further in the perspective of the international bodies that facilitate the dispute. This research uses normative legal research methods